EVALUASI KURIKULUM PROGRAM KEAHLIAN TEKNIK KOMPUTER DAN JARINGAN SMKN 2 WATAMPONE DI KABUPATEN BONE SULAWESI SELATAN Hasbullah - HASBULLAH Ulla (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract. This research is motivated by the fact that graduates of SMK are considered not flexible in adjusting to changes in the workplace, only having a single or specific skill that is quickly obsolete. In addition, there is a gap between schools and industry in terms of curriculum that makes students rigid when involved in the world of work and the industrial world. The general problem formulation in this research is how is the quality of the implementation of the computer and network engineering expertise program at SMKN Bone Regency of South Sulawesi? Specifically, (1) What is the quality of the implementation of the process aspects of the computer and network engineering expertise program? (2) What is the quality of the product aspects of the computer and network engineering expertise program? The purpose of this research is to find out the quality of the implementation of computer and network engineering expertise programs in the Bone Regency of South Sulawesi. The method in this study uses descriptive evaluative with quantitative research approaches. The population is the SMKN majoring in computer and network engineering in the Bone District of South Sulawesi consisting of principals, teachers and students. There were 52 students taken using stratification random sampling technique. The instruments used were questionnaire, interview, documentation study. This research uses descriptive data analysis. The results showed that in general the quality of program implementation was going well. This can be seen from the two aspects that were specifically examined namely the aspects of the process obtained from the questionnaire relating to the perceptions of students and teachers have been going well because it is in accordance with curriculum documents. In the aspect of product / results obtained from the study of documents relating to student learning outcomes data both theory and practice have been going well because it is in accordance with the planned objectives.K